'Impossibly erotic things': On men's underwear in Brief Encounters by Suzanne Forster. Issue 2 (1st August 2022) - Allan, Jonathan A.
Romance novels are known for their sexy heroes who grace the covers and pages. This article concerns itself with how heroes are dressed; in particular, I consider the role of men's underwear in Brief Encounters by Suzanne Forster. Brief Encounters is a Harlequin Romance novel and, more specifically, a Harlequin Blaze. By way of close textual engagement, I show that men's underwear plays a significant role in the narrative, especially with respect to the construction and representation of sexuality and masculinity. To these ends, I argue that Brief Encounters imagines men's underwear as being more than functional, but as desirable and erotic. This article thus contributes to scholarship at the intersection of popular culture studies and critical studies of men's fashion.